New Records of Predators of the Meliaceae Shoot Borer Hypsipyla robusta Moore (Lepidoptera: Pyralidae) - Singh, Pratap; Misra, Ram Mohan (Indian Forester, 1988)
The Meliaceae shoot borer Hypsipyla robusta Moore an important pest of trees belonging to family Meliaceae. A survey for the predators of H. robusta in Doon Valley revealed five predators including one reduvid, one formicid, two carabids, one mantid, common myna and five striped squirrel were recorded for the first time. A brief account of the predators and their potentialities are given in this paper.